Mapping Research Trends on Emotional Intelligence and Leadership: A Bibliometric Analysis - Joshua Michael H. Balitustus; Norielle L. Sarmiento; Abegail U. Tayam; Jennifer P. Solis (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study investigates emotional intelligence with respect to leadership research by analyzing 1881 Scopus-indexed relevant documents from between 1952 and 2024. Through bibliometric analysis using VOSviewer and the Bibliometrix package in R, the mapping has been analyzed for publication trends, leading authors, influential journals, conceptual themes, and global collaboration networks. The results reveal scholarly activity moving slowly at first but then accelerating significantly starting in 2010, which coincides with the growing recognition of emotional intelligence as an important factor in effective leadership and high organizational performance. Some notable authors are Boyatzis, Stoller, and Humphrey whose works are tending to be referred to for continuing to shape research development. The analysis of themes denotes two major areas: (1) Individual emotional skill, psychological dimension, and personality trait-centered research and (2) studies on the use of emotional intelligence in leadership, teamwork, interaction, and organizational management in workplaces. Integration of Emotional Intelligence theory with leadership practice is still limited despite a good number of publications, as much output is concentrated in management and healthcare, with many other industries missing out. Moreover, collaboration patterns indicate strong inputs from Western countries while developing regions remain less visible. These results imply that, despite the further development of the area, there are considerable gaps in the research, especially regarding the integration of emotional intelligence and online leadership situations, management teams, and artificial-intelligence-based organizational frameworks, and in the cross-cultural and underrepresented regional contexts.